Alces americanus subsp. americanus Clinton 1822 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Alces americanus subsp. americanus Clinton 1822 Alces americanus subsp. americanus Clinton 1822, Letters on the natural history … of New York: 193. Type Locality: "Country north of Whitestown". USA, New York, probably in the western Adirondack region. Synonyms: Alces americanus subsp. andersoni Peterson 1950; Alces americanus subsp. buturlini Chernyavsky and Zhelesnov 1982; Alces americanus subsp. columbae Lydekker 1915; Alces americanus subsp. gigas Miller 1899; Alces americanus subsp. lobatus (Agassiz 1846); Alces americanus subsp. meridionalis Matschie 1913; Alces americanus subsp. muswa Richardson 1852; Alces americanus subsp. pfizenmayeri Zukowsky 1910; Alces americanus subsp. shirasi Nelson 1914; Alces americanus subsp. yakutskensis Millais 1911. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Artiodactyla, pp. 637-722 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 653, DOI: 10.5281/zenodo.7316519